AGRICULTURAL FRANCHISING AND CONTRIBUTION TO ACHIEVING OBJECTIVES OF THE EU COMMON AGRICULTURAL POLICY - Stanković, Milica (Economics of Agriculture, 2018)
The Common Agricultural Policy is the oldest, the most complex, the most expensive EU policy and it represents one of the most important drivers of European integration. Agrarian franchising is one of the innovations in the fled of franchising, which implementation is still in its infancy and it is necessary to strive for the popularization of this business model. The aim of the paper is to emphasize the importance of agricultural franchising concept development and contribution of implementation of this concept to the achievement of the Common Agricultural Policy objectives and improvement of the agrarian sector as a whole. Special attention is paid on agricultural franchising as a hybrid form of disinvestment in conditions of economic crisis. Based on analysis of advantages and disadvantages of agricultural franchising, we conclude that it has the potential for solving a large number of problems that occur in the agrarian sector, with a particular focus on the importance of agricultural franchising to the achievement of the CAP objectives.